The association between comorbidity and physical activity levels in people with osteoarthritis: Secondary analysis from two randomised controlled trials. Issue 2 (June 2020) - McKevitt, Sarah; Healey, Emma; Jinks, Clare; Rathod-Mistry, Trishna; Quicke, Jonathan
Abstract : Objective: To determine whether comorbidity presence, frequency or type is associated with Physical Activity (PA) levels in people with Osteoarthritis (OA). Design: Secondary data analysis of adults aged ≥45, with OA related pain recruited to the BEEP trial (knee pain, n = 514) (ISRCTN93634563) and the MOSAICS trial (peripheral joint pain, n = 525) (ISRCTN06984617). Comorbidities considered were respiratory, cardiovascular diseases (CVD), depression, type 2 diabetes and obesity. Self-report PA was measured using the Physical Activity Scale for the Elderly (PASE). Linear regression models were used to estimate the mean change (β) in PA with comorbidity presence, frequency and type adjusting for potential confounding covariates. Results: In the BEEP trial comorbidity presence was associated with a decrease in PASE score (β = -32.25 [95% confidence interval (95% CI) −48.57, −15.93]). Each additional comorbidity was associated with an incrementally lower PASE score, one comorbidity (β = −24.42 [-42.45, −6.38]), two comorbidities β = −34.76 [-56.05, −13.48]), and three or more comorbidities β = −73.71 [-106.84, −40.58]) compared to those with no comorbidity. This pattern was similar in MOSAICS, but with a plateau in association from two comorbidities onward. In BEEP and MOSAICS, respiratory (β = −40.60 [-60.50, −20.35]; β = −11.82 [-34.95, 11.31]) and CVD (β = −27.15 [-53.25, −1.05]; β = −30.84 [-51.89, −9.80]) comorbidities were associated with the largest reduction in PASE scores respectively. Conclusion: Comorbidity presence and frequency is associated with lower PA levels and respiratory and CVD comorbidities have the greatest impact. Future exploratory work needs to be done to understand how and why comorbidity is associated with PA levels in people with OA.